Nitric oxide-mediated inhibition of phenylephrine-induced contraction in response to hypothermia is partially modulated by endothelial Rho-kinase - Lee, Soo Hee (Int J Med Sci, 2020)
This study examined the possible upstream cellular signaling pathway associated with nitric oxide (NO)-mediated inhibition of phenylephrine-induced contraction in isolated rat aortae in response to mild hypothermia, with a particular focus on endothelial Rho-kinase. We examined the effects of mild hypothermia (33°C), wortmannin, N(ω)-nitro-L-arginine methyl ester (L-NAME), Y-27632, 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) and methylene blue, alone and combined, on phenylephrine-induced contraction in isolated rat aortae. Finally, we examined the effects of mild hypothermia, wortmannin, Y-27632 and L-NAME, alone and combined, on endothelial nitric oxide synthase (eNOS) and endothelial Rho-kinase membrane translocation induced by phenylephrine. Mild hypothermia attenuated phenylephrine-induced contraction only in endothelium-intact aortae. L-NAME, wortmannin, ODQ and methylene blue increased phenylephrine-induced contraction of endothelium-intact aortae pretreated at 33°C. Wortmannin did not significantly alter the L-NAME-induced enhancement of phenylephrine-induced maximal contraction of endothelium-intact aortae pretreated at 33°C. Wortmannin abolished the ability of Y-27632 to magnify the hypothermic inhibition of maximal phenylephrine-induced contraction. Wortmannin and L-NAME inhibited the enhancing effect of mild hypothermia on phenylephrine-induced eNOS phosphorylation. Y-27632 and L-NAME attenuated the enhancing effect of hypothermia on phenylephrine-induced endothelial Rho-kinase membrane translocation. The results suggest that hypothermia-induced, NO-dependent inhibition of phenylephrine-induced contraction is mediated by phosphoinositide 3-kinase and inhibited by endothelial Rho-kinase activation.